The Importance of Haemogram Parameters in the Diagnosis and Prognosis of Septic Patients - Orfanu, Alina Elena (J Crit Care Med (Targu Mures), 2017)
Sepsis represents a severe pathology that requires both rapid and precise positive and differential diagnosis to identify patients who need immediate antimicrobial therapy. Monitoring septic patients’ outcome leads to prolonged hospitalisation and antibacterial therapy, often accompanied by substantial side effects, complications and a high mortality risk. Septic patients present with complex pathophysiological and immunological disorders and with a predominance of pro-inflammatory or anti-inflammatory mediators which are heterogeneous with respect to the infectious focus, the aetiology of sepsis or patients’ immune status or comorbidities. Previous studies performed have analysed inflammatory biomarkers, but a test or combinations of tests that can quickly and precisely establish a diagnosis or prognosis of septic patients has yet to be discovered. Recent research has focused on re-analysing older accessible parameters found in the complete blood count to determine the sensitivity, specificity, positive and negative predictive values for the diagnosis and prognosis of sepsis. The neutrophil/lymphocyte count ratio (NLCR), mean platelet volume (MPV) and red blood cells distribution width (RDW) are haemogram indicators which have been evaluated and which are of proven use in septic patients’ management.